Pengaruh Biaya Operasional Pendapatan Operasional, Capital Adequacy Ratio Dan Resiko Kredit Terhadap Profitabilitas Pada Bank Umum BUMN Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2010 - 2020 - Renal Adi Prayoga; Didit Supriyadi; Nunung Nurhasanah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study was conducted to examine the effect of Operating Costs on Operating Income, Capital Adequacy Ratio (CAR) and credit risk on profitability (ROA). The problems discussed are (1) Does the Operating Cost of Operating Income affect profitability, (2) Does the Capital Adequacy Ratio (CAR) affect profitability, (3) Does credit risk have a significant effect on profitability (4) Does the Operational Cost of Operating Income, Capital Adequacy Ratio (CAR) and credit risk simultaneously have a significant effect on profitability. The data used in the study was obtained from the Financial Statements of the publications of state-owned banks listed on the Indonesia Stock Exchange (IDX) for the 2010-2020 period. The data analysis technique used is multiple linear regression. The results of this study indicate that the Operating Cost of Operating Income (BOPO) has a significant but negative effect on profitability, Capital Adequacy Ratio (CAR) has no significant and negative effect on profitability, credit risk has a positive and significant effect on profitability. Simultaneously shows the results that the Operational Cost of Operating Income (BOPO), Capital Adequacy Ratio (CAR) and credit risk have a significant effect on the profitability of state-owned commercial banks for the 2010-2020 period. Keywords: Bopo, car, credit risk, profitability